A Narrative on Experiences of a Couple with Physical Disabilities in the Adoption Process - Povilaitienė, Neringa; Kubilienė, Kristina (Social Welfare: Interdisciplinary Approach, 2025)
The article analyses the experiences of the couple with physical disabilities in the adoption process, their feelings in encountering infertility problems, the society’s attitude towards persons with physical disabilities, their stigmatisation. The paper presents the results of the research on adoption experiences of persons with physical disabilities. The obtained results demonstrate that the couple with physical disabilities encounters a medical approach to persons with mobility disabilities. The research has revealed that persons with physical disabilities encounter negative attitudes of healthcare professionals in the adoption process and that the approach of these professionals often lacks tolerance and respect. Based on the research, it was found that the couple with physical disabilities had unfounded fears and doubts about the adoption team’s attitude towards their disability. However, it should be emphasised that professionalism and non-stereotypical approach of the adoption team ensure equal opportunities of the couple with physical disabilities to take part in training, discussions and workshops. Courts also do not emphasise the physical disability as an obstacle in the adoption process. Research data shows that adoptive parents with physical disabilities feel anxious and are aware of the challenges that may arise as their child grows up in relation to society’s view on them as parents with physical disabilities.
Keywords: adoption; persons with physical disabilities; experiences